Assessment of Negative Symptoms in Schizophrenia: From the Consensus Conference-Derived Scales to Remote Digital Phenotyping - Armida Mucci; Stefan Leucht; Giulia M. Giordano; Luigi Giuliani; Sophia Wehr; Lucia Weigel; Silvana Galderisi (Brain Sciences)
The assessment of negative symptoms in schizophrenia has advanced since the 2006 NIMH-MATRICS Consensus Statement, leading to the development of second-generation rating scales like the Brief Negative Symptom Scale and the Clinical Assessment Interview for Negative Symptoms. These scales address the limitations of first-generation tools, such as the inclusion of aspects that are not negative symptoms and the lack of assessment of the subject’s internal experience. However, psychometric validation of these scales is still in progress, and they are not yet recommended by regulatory agencies, thus limiting their use in clinical trials and settings. Complementing these traditional methods, remote digital phenotyping offers a novel approach by leveraging smartphones and wearable technology to capture real-time, high-resolution clinical data. Despite the potential to overcome traditional assessment barriers, challenges remain in aligning these digital measures with clinical ratings and ensuring data security. Equally important is patient acceptance, as the success of remote digital phenotyping relies on the willingness of patients to use these technologies. This review provides a critical overview of both second-generation scales and remote digital phenotyping for assessing negative symptoms, highlighting future research needs.